2019
DOI: 10.1016/j.bjps.2019.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Computerised adaptive testing accurately predicts CLEFT-Q scores by selecting fewer, more patient-focused questions

Abstract: Background: The International Consortium for Health Outcome Measurement (ICHOM) has recently agreed upon a core outcome set for the comprehensive appraisal of cleft care, which puts a greater emphasis on patient-reported outcome measures (PROMs) and, in particular, the CLEFT-Q. The CLEFT-Q comprises 12 scales with a total of 110 items, aimed to be answered by children as young as 8 years old. Objective: In this study, we aimed to use computerised adaptive testing (CAT) to reduce the number of items needed to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 27 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…For example, if we know that Nose scores and Nostrils scores correlate, and that a respondent has attained a high score in the Nose scale, it may be more appropriate to start a Nostril scale CAT with a question targeted towards respondents with a higher Nostrils score. Future work will determine whether the accuracy and efficiency of the CLEFT-Q CAT scales 17 could be improved with multidimensional item response theory.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if we know that Nose scores and Nostrils scores correlate, and that a respondent has attained a high score in the Nose scale, it may be more appropriate to start a Nostril scale CAT with a question targeted towards respondents with a higher Nostrils score. Future work will determine whether the accuracy and efficiency of the CLEFT-Q CAT scales 17 could be improved with multidimensional item response theory.…”
Section: Discussionmentioning
confidence: 99%
“…Timing of administration of the CLEFT-Q is crucial; in routine clinical practice, for example, detailed questions about facial appearance could be asked when the surgical window is opening up. In addition, to reduce patient burden, a computer adaptive testing (CAT) version of the 12 CLEFT-Q scales has been developed (Harrison et al, 2019). In the CAT version, the number of questions that participants needed to answer was reduced to an average of 43 items while maintaining a 97% correlation between scores obtained with CAT and full-length scales.…”
Section: Discussionmentioning
confidence: 99%
“…If the instrument had been administered electronically, scales could have been automatically presented to patients depending on age and diagnosis. Computerized adaptive testing (CAT) has been evaluated with CLEFT-Q ( Harrison et al, 2019 ). The study showed that 97% accuracy of final result could be obtained by using only 43 items (39.2%) of the 110 items in the full scale.…”
Section: Discussionmentioning
confidence: 99%